2005
DOI: 10.1063/1.1883720
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid-phase growth in microcrystalline silicon thin films deposited by plasma enhanced chemical vapor deposition at low temperatures

Abstract: Crystallographic studies on microcrystalline silicon (μc-Si) films, which were prepared by very-high-frequency plasma-enhanced chemical vapor deposition at a low temperature of 180°C, have been performed employing thickness evolutions of x-ray and electron diffraction measurements. The experimental results revealed that amorphous phase in μc-Si is transited to crystalline phase in solid phase in whole region from the top to the bottom, and the transition to the (220) orientation is dominantly found. These grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Raman scattering measurements revealed that the prepared lc-Si films were in the amorphous-crystalline transition region with the crystalline fractions of 42-66% [12]. The degree of (2 2 0) preferential orientation, I (220) /I (111) , where I (hkl) denotes the integrated intensity of X-ray diffraction at Si(h k l) plane, revealed that the crystallographic preferential orientations of lc-Si films were varied from (1 1 1) plane to (2 2 0) plane.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Raman scattering measurements revealed that the prepared lc-Si films were in the amorphous-crystalline transition region with the crystalline fractions of 42-66% [12]. The degree of (2 2 0) preferential orientation, I (220) /I (111) , where I (hkl) denotes the integrated intensity of X-ray diffraction at Si(h k l) plane, revealed that the crystallographic preferential orientations of lc-Si films were varied from (1 1 1) plane to (2 2 0) plane.…”
Section: Resultsmentioning
confidence: 99%
“…Undoped lc-Si films were prepared by very-high-frequency (VHF) (100 MHz) plasma enhanced chemical vapor deposition (PECVD) at a substrate temperature of 180°C [12]. The cumulative thicknesses, d, which were estimated from the deposition time, t, were 0.5-4 lm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to break the tendency, fundamental material properties of high-growth-rate lc-Si should be investigated. In our previous reports [9][10][11][12][13], we have reported structural properties of low-growth-rate (<0.5 nm/s) lc-Si centered upon the lc-Si deposited at 0.38 nm/s used as the i-layer of 9% efficiency solar cell, and summarized the structural features required for the device-grade lc-Si.…”
Section: Introductionmentioning
confidence: 99%